Competitive swimmers with hypermobility have strength and fatigue deficits in shoulder medial rotation - Liaghat, B.; Juul-Kristensen, B.; Frydendal, T.; Larsen, C. M.; Søgaard, K.; Salo, A. I. T. (Journal of Electromyography and Kinesiology, 2018)
Generalised Joint Hypermobility including shoulder hypermobility (GJHS) in swimmers is considered an intrinsic risk factor for shoulder injuries. The aim was to investigate the association of GJHS with shoulder strength, fatigue development and muscle activity during swimming-related shoulder rotations. Totally, 38 competitive swimmers (aged 13-17 years) participated, 19 were competitive swimmers with GJHS and 19 were age, sex and club matched swimmers without GJHS. Concentric isokinetic force in medial and lateral rotations were measured at 60°/s (5 repetitions) and 180°/s (10 repetitions). Electromyographic activity was measured from upper trapezius, lower trapezius, serratus anterior, infraspinatus and pectoralis major muscles. Swimmers with GJHS produced significantly lower peak torque (0.53 vs. 0.60 Nm/kg; p = .047) and maximum work (0.62 vs. 0.71 J/kg; p = .031) than controls during medial rotation (60°/s). Swimmers with GJHS showed significantly larger isokinetic fatigue at 180°/s (0.321 J/repetition; p = .010), and tendencies to lower levels of muscle activity in infraspinatus (20%, p = .066) and pectoralis major (34%, p = .092) at 60°/s during medial rotation. Young competitive swimmers with GJHS, despite no formal diagnosis, displayed strength and fatigue deficits in medial rotation, potentially inherent with greater risk of shoulder injury. Whether GJHS swimmers benefit from medial rotation strengthening is an important topic for future studies.